Standards of the Polish Ultrasound Society – Update. Ultrasound examination of renal arteries - Anna Drelich-Zbroja (Journal of Ultrasonography, 2014)
This paper has been prepared on the basis of the Standards of the Polish Ultrasound Society and updated based on the latest reports from the relevant literature. The author presents a renal artery examination technique, patient preparation for the testing, limitations of the method, currently recommended proper blood flow standards and criteria for the diagnosis of significant stenoses. Renal artery ultrasound is performed using a 2–5 MHz probe, usually a convex 3.5 MHz one. The ultrasound machine must be equipped with the Doppler options for the evaluation of color coded blood flow and recording of the blood flow spectrum, including the triplex Doppler mode. Patients have to fast for at least eight hours before testing. Ultrasound always begins with the assessment of renal structure using the grayscale. Next, color coded blood flow imaging is used, followed by placing a sampling gate in the lumen of the target vessel to record the spectral image. The aim of renal artery ultrasound is to assess the course and position of arteries, evaluate blood flow parameters, as well as visualize possible changes: stenoses, occlusions, aneurysms, or arteriovenous fistulas. Blood flow velocity is always measured in a longitudinal projection/ longitudinal section of the vessel, after placing the sampling gate in the central part of the flowing bloodstream, which normally corresponds to the central part of the vascular cross-section. When diagnosing renal artery stenosis, it is necessary to know the nature of the blood flow and norms for flow parameters in healthy vessels. The spectrum of the blood flow velocity in renal arteries and their branches is a low resistance one. The following parameters are used to evaluate normal renal arteries and to identify the narrowed ones: Vmax, Vmin, RAR, AT, AI, RI and PI.